It doesn't have to hurt : your smart guide to a pain-free life - Gupta, Sanjay, 1969- (Simon & Schuster, 2025)
"Are you one of the 52 million people who experience chronic pain in your day-to-day life? In It Doesn't Have to Hurt, Sanjay Gupta makes the empowering argument that there are effective options for relief that you can start practicing today to greatly reduce your chances of suffering pain tomorrow. The significance of reducing and even eliminating pain cannot be overstated. Gupta shows how pain carries an enormous amount of physical, social, and emotional baggage, which is, in part, why it has been so hard to treat, and too often ignored. It can also present in infinite ways. Yet both patients and practitioners labor under the mistaken idea that most pain problems can be fixed with a drug or procedure. It turns out we have tremendous agency in choosing how we'll respond. The brain "creates" pain, but it also has the capacity to reduce or even eliminate it. There is more evidence than ever about the benefits of sleep, diet and nutrition, mindfulness-based pain management (MBPM), myofascial and other hands-on treatments, as well as yoga, specialized psychotherapies, and even social "prescriptions" -- prompting more doctors than ever to focus on these solutions. Gupta runs the gamut of conventional and complementary approaches, including the technique known as Mobilization Exercise Analgesia Treatment, foam rolling, acupuncture, trigger point injections, and vital "prehabilitation" before any operation. He shares how to make sense of all those over-the-counter pills, patches, and pain products, as well as drugs advertised on television or prescribed by your doctors. He covers psychedelics, supplements, and CBD. And he highlights insights from some of the nation's leading pain scientists and specialists, plus stories of challenge and triumph over pain by those with lived experience." --